[Political Protest Communication to The Authorities (Critical Discourse Analysis of Norman Fairclough on Robin of Sherewood by Teater Katak)] - Christina Tandaju (SEMIOTIKA: Jurnal Komunikasi, 2021)
The leadership crisis is an interesting thing to discuss in the current era, where everyone wants to gain power and is upheld by the people under him. However, the power that has been obtained is not the least bit misused properly, a person should rule and lead his people. Social issues regarding corruption, oppression of the little people, arbitrary tax increases, dishonesty from the leaders themselves, are certainly very close to our ears about the political and social conditions that exist in Indonesia. The Robin of Sherewood performance from the KataK Theater, directed and written by Venantinus Vladimir Ivan, raised this with satires in the form of dialogue that was brought up during the performance which took place at the Jakarta Arts Building on 11-13 May 2018. The political communication of protest is reflected in this performance, how Loxely and the rest of Robin are a reflection of those who dare to cast a voice of truth. To further analyze the Robin of Sherewood performance from the KataK Theater, researchers used critical discourse analysis developed by Norman Fairclough. In his analysis, Fairclough divides discourse analysis into three major aspects, namely: Microstructure Analysis (Text), Mesostructural Analysis (Performance Production), Macrostructural Analysis (Situational, Institutional, Social) (Eriyanto, 2018: 286). This research uses qualitative research methods, supported by a critical paradigm and also a critical tradition. The results of this study indicate that it has been shown how a theater performance can reflect, entertain and educate the audience regarding the political communication of protest contained therein through dialogues that are reflected in each act. Criticism of the authorities, conveying what feels right, and defending the oppressed people are continuous with the current political conditions in Indonesia. All these aspects are packaged neatly and attractively..